2016
DOI: 10.1155/2016/9850473
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Physicians’ Attitudes towards Accessing Mental Health Resources

Abstract: Despite their rigorous training, studies have shown that physicians experience higher rates of mental illness, substance abuse, and suicide compared to the general population. An online questionnaire was sent to a random sample of physicians across Canada to assess physicians' knowledge of the incidence of mental illness among physicians and their attitudes towards disclosure and treatment in a hypothetical situation where one developed a mental illness. We received 139 responses reflecting mostly primary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…We have operationalized, and complied with others regarding the policing the profession. The time is ripe to balance the needs and interests of physicians in high quality confidential treatment [20,62,63] with those of public safety, and to preserve the confidentiality of proceedings against physicians until such time as there is a finding of incompetence requiring disclosure to protect the public. In the United States, the Federation of State Medical Boards, Federation of State Physician Health Programs, and physician advocacy groups have critical roles to play in improving physician health and decreasing physician death by suicide.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have operationalized, and complied with others regarding the policing the profession. The time is ripe to balance the needs and interests of physicians in high quality confidential treatment [20,62,63] with those of public safety, and to preserve the confidentiality of proceedings against physicians until such time as there is a finding of incompetence requiring disclosure to protect the public. In the United States, the Federation of State Medical Boards, Federation of State Physician Health Programs, and physician advocacy groups have critical roles to play in improving physician health and decreasing physician death by suicide.…”
Section: Resultsmentioning
confidence: 99%
“…One half of all students experience burnout, and a similar number of practicing physicians experience feelings of exhaustion, loss of enthusiasm, cynicism and decreased personal accomplishment [17,18]. Students' anxiety and depression also may develop during this time of training, particularly as they transition from classroom education to the clinical years [19], within a society that fosters the erroneous belief among physicians that they are invincible or somehow invulnerable to illness [20].…”
mentioning
confidence: 99%
“…11 A study to identify factors preventing Canadian physicians (mostly primary care physicians and nonsurgical specialists) from accessing mental health services showed that the most important factors influencing a physician's decision to disclose their illness included career implications, professional integrity and social stigma. 24 An anonymous, UK-wide online survey of physicians with and without a history of mental illness investigated physician attitudes about disclosing mental illness. This study showed that trainees and younger physicians were less likely to disclose mental ill health than general practitioners and consultants due to concerns about labeling, confidentiality, and not understanding available support structures.…”
Section: Right Of Physicians To Access Confidential Mental Health Sermentioning
confidence: 99%
“…Some of them have been focussed in rating attitudes towards mental illness at the sociallevel on general populations/communities by simply analyzing the effect of sex, age, country, and so on (see, for instance, [10,20,21,27,37]). Other studies have concerned attitudes of medical/health care students ('tommorrow's' doctors) and non-psychiatric physicians (see, for instance, [1,2,3,8,9,12,13,15,16,21,22,33,34,35,40,42,46]) and some few are devoted to compare attitudes of psychiatrists, psychiatric nurses and relatives of mental patients in contrast to the general population (see, for instance, [39]). Also some others, like [38], deal with a comparative analysis of beliefs and attitudes among different countries.…”
Section: Introductionmentioning
confidence: 99%
“…This paper aims to perform a comparison of attitudes towards mental illness of three groups of nonpsychiatric physicians (more concretely, primary care doctors, neurologists and internists). Although a few attempts to such a comparative analysis can be found in the literature (see [4,16,30,36]), and the need for eliminating the stigmatization and discrimination within the medical profession has been often claimed (see [28]), the topic has not yet received a deep research attention.…”
Section: Introductionmentioning
confidence: 99%